Estimating direct and indirect genetic effects on offspring phenotypes using genome-wide summary results data - Nicole M. Warrington (Nature Portfolio, 2021)
Estimating direct and indirect effects of genotypes on phenotypes is important for genetic analyses such as Mendelian randomization. Here the authors compare five different methods to estimate direct and indirect genetic effects using summary results statistics that account for sample overlap.